LINGKUNGAN KELUARGA DAN PERGAULAN REMAJA YANG BERISIKO MELAKUKAN PENYALAHGUNAAN NARKOBA - Muslihatun, Wafi Nur; Santi, Mina Yumei (Jurnal Kesehatan Ibu dan Anak, 2015)
Drug abuse among adolescentare increasing in lndonesia. Family conditions and adolescent promiscuity is one of the main risk factors in adolescents fo drug abuse. This study aims to determine the condition of the family and the kind of adolescent promiscuity who are at risk of drug abuse in SMK YPKK Ambarketawang Sleman, Yogyakarla. This study is a cross sectional analytic study design, using a sample of 74 people with simple random sampling. The analysis showed family environment (p = 0.025 with OR = 1.763;95% Cl = 1.430 to 2.173) and adolescent promiscuity are associated risk of drug abuse (p=0.009 with OR= 10,182;95% Cl = 1.245 to 83.249). Adolescent who do not like to take advice of parents(p= 0.031 with OR=4.909;95% Cl=1.010 to 23.857),do not like friend who obey the religion (p = 0.031 with OR = 4.909; 95% Cl = 1.010 to 23.857), feel pleased   together with friends than with parents (p = 0.015 with OR = 9.059; 95% Cl = 1.101 to 74.521), do not utilize the free time with the family (p= 0.025 with OR = 8.000; 95 % Cl = 1 .965 to 66.306) are at risk to drug abuse. Conclusion: adolescents with familiy environment and promiscuity are not goad take a greater risk of drug abuse. Suggested always create a good family environment and adolescents promiscuity to avoid the riskof drug abuse.